Between Security and Spectatorship: The Media of Transnational Mobility at Canadian Airports - Hart, Sydney (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
As crucial nodes for networks of globalization and border security, Canada’s major international airports include a wide range of media for the visual representation of human mobility, including artistic and cultural displays, biometric imaging, and x-ray scans. Does the visuality of media at airport security bear any epistemological relation to the visuality of art and cultural displays at airports? This paper analyzes the cultural patterns that come into focus when processes of security and spectatorship are examined through forms of power such as pastoral power and governmentality. Furthermore, Canada’s major airports order mobility and security through modes of symbolic representation, thereby playing significant educational roles. Visual media at these airports thereby educate travelers on ways of navigating space, while obscuring the movements of those most negatively impacted by differential mobility.